Interferon regulatory factor-5-dependent CD11c+ macrophages contribute to the formation of rupture–prone atherosclerotic plaques. (9th February 2022) - Edsfeldt, Andreas; Swart, Maarten; Singh, Pratibha; Dib, Lea; Sun, Jiangming; Cole, Jennifer E.; Park, Inhye; Al-Sharify, Dania; Persson, Ana; Nitulescu, Mihaela; Borges, Patricia Das Neves; Kassiteridi, Christina; et al.
Abstract: Aims: Inflammation is a key factor in atherosclerosis. The transcription factor interferon regulatory factor-5 (IRF5) drives macrophages towards a pro-inflammatory state. We investigated the role of IRF5 in human atherosclerosis and plaque stability. Methods and results: Bulk RNA sequencing from the Carotid Plaque Imaging Project biobank were used to mine associations between major macrophage associated genes and transcription factors and human symptomatic carotid disease. Immunohistochemistry, proximity extension assays, and Helios cytometry by time of flight (CyTOF) were used for validation. The effect of IRF5 deficiency on carotid plaque phenotype and rupture in ApoE −/− mice was studied in an inducible model of plaque rupture. Interferon regulatory factor-5 and ITGAX/CD11c were identified as the macrophage associated genes with the strongest associations with symptomatic carotid disease. Expression of IRF5 and ITGAX/CD11c correlated with the vulnerability index, pro-inflammatory plaque cytokine levels, necrotic core area, and with each other. Macrophages were the predominant CD11c-expressing immune cells in the plaque by CyTOF and immunohistochemistry. Interferon regulatory factor-5 immunopositive areas were predominantly found within CD11c + areas with a predilection for the shoulder region, the area of the human plaque most prone to rupture. Accordingly, an inducible plaque rupture model of ApoE −/− Irf5 −/− mice had significantly lower frequencies of carotid plaque ruptures, smaller necrotic cores, and less CD11c + macrophages than their IRF5-competent counterparts. Conclusion: Using complementary evidence from data from human carotid endarterectomies and a murine model of inducible rupture of carotid artery plaque in IRF5-deficient mice, we demonstrate a mechanistic link between the pro-inflammatory transcription factor IRF5, macrophage phenotype, plaque inflammation, and its vulnerability to rupture. Structured Graphical Abstract: Macrophages perform both pro- and anti-atherogenic functions depending on their transcriptional status and activation. Using human carotid endarterectomies and a murine model of inducible rupture of carotid plaque, we show that the transcription factor interferon regulatory factor-5 (IRF5) promotes macrophage activation with the production of chemokines CCL2 and CCL4, and the expression of the integrin CD11c, while it disables the production of proteins required for the uptake of apoptotic cells within the plaque (efferocytosis) such as MFEG8 and the integrin ITGB3. In doing so, IRF5 promotes inflammation and increases the necrotic core size enhancing plaque vulnerability to rupture. MFGE8, Milk fat globule—epidermal growth factor—factor VIII; CCL2, C–C motif chemokine ligand 2; CCL4, C–C motif chemokine ligand 4; ITGB3, Integrin subunit beta 3.